ANALISIS PENERAPAN BASE TRANSCEIVER STATION HIGH CAPACITY PADA GLOBAL SYSTEM FOR MOBILE COMMUCATION - Agoes, Suhartati; Nelly, Nelly (Jurnal Teknik Elektro, 2010)
High Capacity Base Transceiver Station (Hi-Cap BTS) is one kind of BTS which can hold increased traffic load rapidly because the numbers Trx at each sector can reach twelve Trx. Because of the fact, on the other hand the capacity of Hi-Cap BTS Trx are four times more than generally BTS. This paper discusses about the result and the analysis of Hi-Cap BTS implementation on BTS Muspasarseni with the first Trx configuration is 4/4/3 be modified to 8/6/3. This case uses four parameters such as traffic, Drop Call Rate (DCR), Handover Success Rate (HOSR) and Stand-alone Dedicated Control Channel (SDCCH) Success Rate (SDSR). Based on the analysis that has been performed, traffic rate at sector one, two and three are increased to 134%, 65%, 4% respectively. DCR rate at sector one, two and three are decreased to 54%, 39%, 18% respectively. HOSR rate at sector one, two and three are increased to 10%, 2,6%, 1,5% respectively. SDSR rate at sector one and two are increased to 2,3%, 2,8%, but SDSR rate at sector three is decreased to 1,2%. Keywords: BTS Hi-Cap, DCR, HOSR, SDSR